PENINGKATAN KETERAMPILAN LOMPAT JAUH MELALUI MEDIA KARDUS PADA SISWA KELAS IV SEKOLAH DASAR NEGERI 09 TEBAT KARAI KABUPATEN KEPAHIANG - Ripaldo, Hendrio; Martiani, Martiani; Sembiring, Lina Tri Astuty (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
Abstract This study aims to determine the improvement of long jump skills through cardboard box media on students of class IV state elementary school 09 Tebat Karai, Kepahiang Regency in the 2022/2023 academic year. This research is a Classroom Action Research (PTK) which lasts for two cycles, each cycle consisting of three meetings. The research subjects were fourth grade students at SD Negeri 09 Tebat Karai, Kepahiang Regency, totaling 23 students. Data collection methods used are observation methods, long jump tests, and documentation. Data analysis techniques were carried out by analyzing teacher observation data and analyzing long jump skill test data. The results showed that long jump learning through cardboard box jumps for two cycles could be increased. The average score of students in cycle 1 was 56.52% or as many as 13 students who achieved the KKM score from the provisions of 85%. In cycle II the average increased to 91.3% or as many as 21 students who achieved a KKM score of 85%. This proves that long jump using cardboard box media is very effective for improving long jump skills.